Effects of Shiga-Toxin Producing Strains of Escherichia coli (STEC), Lead and Bisphenol A Mixture on Kidney and Spleen of Whistler Mice - Omoruyi, Iyekhoetin Matthew; Enabulele, Stephen Amadin; Omogbare, Sikpojie Raymond (Journal of Science and Technology, 2018)
Human exposure to shiga toxin producing strains of Escherichia coli (STEC), and environmental contaminants such as lead and bisphenol A (BPA) are on the increase globally. This research work was aimed at investigating the effect of these contaminants on the kidney and spleen of Whistler mice when acting singly and in combination. A total of 24 mice (6 groups of 4 mice each) were obtained and feed with STEC, lead and BPA, either singly or in combination, using oral-gastric gavage at a concentration of 5.9 × 105 CFU/ml/bw/day, 60 µg/kg/bw/day and 10 µg/kg/bw/day respectively, for 7 days. After treatment, the mice were sacrificed, and the kidney and spleen observed microscopically by established methods. The results of the current study shows that mice, when administered only STEC, developed interstitial infiltration and congestion of the kidney and spleen respectively, while BPA and Lead, when acting independently, caused durable damages to both organs. Upon administration of two or more of these contaminants together, a somewhat different outcome was recorded, mild damage on both the kidney and spleen. The result therefore shows that exposure to microbial and chemical contaminants singly or together could have grave consequences, and efforts should be made to reduce exposure to these contaminants.